THE EFFECTIVENESS OF MOBILE LEARNING TO INCREASE THE STUDENTS’ READING COMPREHENSION - Fajrin, Nurul (Journal Compound: Improving the Quality of English Education, 2023)
Mobile learning is an innovative educational technology that enhances teaching and learning by leveraging mobile devices for flexible and interactive experiences. This study evaluated the effectiveness of mobile learning in improving reading comprehension among eighth-grade students at an Islamic junior high school in Garut, West Java, Indonesia. Using a quantitative pre-experimental design, 30 students participated in a mobile learning intervention that included interactive tutorials and quizzes on recount texts. Pre-test and post-test assessments revealed significant improvements, with average scores increasing from 76 to 83. Statistical analysis using the Wilcoxon signed-rank test confirmed the results (Sig. = 0.000). While the normalized gain score (0.292) reflected modest overall improvement, the study underscores the potential of mobile learning as a supplementary tool to enhance educational outcomes. Limitations, including the absence of a control group and convenience sampling, highlight the need for further research. Future studies should explore extended interventions and robust methodologies to maximize mobile learning’s impact.